Heaven's Kitchen : Living Religion at God's Love We Deliver. - Bender, Courtney (University of Chicago Press, 2011)
How do people practice religion in their everyday lives? How do our daily encounters with people who hold different religious beliefs shape the way we understand our own moral and spiritual selves? In Heaven's Kitchen, Courtney Bender takes a highly original approach to answering these questions. For more than a year she worked in New York City as a volunteer for a nonprofit, nonreligious organization called God's Love We Deliver, helping to prepare home-cooked meals for people with AIDS. Paying close attention to what was said and not said, Bender traces how the volunteers gave voice to their.